The Pivotal Role of Adipocyte-Na K peptide in Reversing Systemic Inflammation in Obesity and COVID-19 in the Development of Heart Failure - Zi-jian Xie; Joel Novograd; Yaakov Itzkowitz; Ariel Sher; Yosef D. Buchen; Komal Sodhi; Nader G. Abraham; Joseph I. Shapiro (MDPI AG, 2020)
This review summarizes data from several laboratories that have demonstrated a role of the Na/K-ATPase, specifically its α1 subunit, in the generation of reactive oxygen species (ROS) via the negative regulator of Src. Together with Src and other signaling proteins, the Na/K-ATPase forms an oxidant amplification loop (NKAL), amplifies ROS, and participates in cytokines storm in obesity. The development of a peptide fragment of the α1 subunit, NaKtide, has been shown to negatively regulate Src. Several groups showed that the systemic administration of the cell permeable modification of NaKtide (pNaKtide) or its selective delivery to fat tissue-adipocyte specific expression of NaKtide-ameliorate the systemic elevation of inflammatory cytokines seen in chronic obesity. Severe acute respiratory syndrome - coronavirus 2 (SARS-CoV-2), the RNA Coronavirus responsible for the COVID-19 global pandemic, invades cells via the angiotensin converting enzyme 2 (ACE-2) receptor (ACE2R) that is appended in inflamed fat tissue and exacerbates the formation of the cytokines storm. Both obesity and heart and renal failure are well known risks for adverse outcomes in patients infected with COVID-19. White adipocytes express ACE-2 receptors in high concentration, especially in obese patients. Once the virus invades the white adipocyte cell, it creates a COVID19-porphyrin complex which degrades and produces free porphyrin and iron and increases ROS. The increased formation of ROS and activation of the NKAL results in a further potentiated formation of ROS production, and ultimately, adipocyte generation of more inflammatory mediators, leading to systemic cytokines storm and heart failure. Moreover, chronic obesity also results in the reduction of antioxidant genes such as heme oxygenase-1 (HO-1), increasing adipocyte susceptibility to ROS and cytokines. It is the systemic inflammation and cytokine storm which is responsible for many of the adverse outcomes seen with COVID-19 infections in obese subjects, leading to heart failure and death. This review will also describe the potential antioxidant drugs and role of NaKtide and their demonstrated antioxidant effect used as a major strategy for improving obesity and epicardial fat mediated heart failure in the context of the COVID pandemic.